1998
DOI: 10.1074/jbc.273.35.22506
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Interactions between the Anti-apoptotic Protein BAG-1 and Hsc70 Molecular Chaperones

Abstract: The anti-cell death protein BAG-1 binds to 70-kDa heat shock proteins (Hsp70/Hsc70) and modulates their chaperone activity. Among other facilitory roles, BAG-1 may serve as a nucleotide exchange factor for Hsp70/Hsc70 family proteins and thus represents the first example of a eukaryotic homologue of the bacterial co-chaperone GrpE. In this study, the interactions between BAG-1 and Hsc70 are characterized and compared with the analogous GrpE-DnaK bacterial system. In contrast to GrpE, which binds DnaK as a dime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
75
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 104 publications
(79 citation statements)
references
References 48 publications
4
75
0
Order By: Relevance
“…BAG-1 was identi®ed in a screen for bcl-2 binding proteins and has been shown to inhibit apoptosis and promote tumorigenesis (Stuart et al, 1998;Takayama et al, 1995Takayama et al, , 1997. Recent homology cloning identi®ed fragments of at least four other BAG family members, all of which contain a conserved Cterminal domain, the BAG domain (Takayama et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…BAG-1 was identi®ed in a screen for bcl-2 binding proteins and has been shown to inhibit apoptosis and promote tumorigenesis (Stuart et al, 1998;Takayama et al, 1995Takayama et al, , 1997. Recent homology cloning identi®ed fragments of at least four other BAG family members, all of which contain a conserved Cterminal domain, the BAG domain (Takayama et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…There is little other homology between BAG-1 and BAG-3, including lack of the BAG-1L nuclear localization signal or the BAG-1 ubiquitin region. The BAG domain was shown by pull down experiments and functional assays to bind to and promote substrate release from both HSP-70 and HSC-70 (Stuart et al, 1998;Takayama et al, 1997Takayama et al, , 1999. Direct binding of BAG-1 to bcl-2 could not be demonstrated upon direct confrontation, however addition of ATP markedly enhanced BAG-1/bcl-2 binding, suggesting the requirement for an HSP-70 intermediate (Takayama et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…BAG-1 proteins contain a ubiquitin-like domain, the signi®cance of which is presently unknown, and several copies of a EE (A/V/L/ M)T(Q/R/K)(S/T) repeat. The carboxyl-domain of BAG-1 is required for Hsp70/Hsc70 binding and shows weak amino acid sequence homology with bacterial GrpE, an ADP/ATP exchange factor for the prokaryotic chaperone DNaJ (Stuart et al, 1998;Hartl, 1996). In this regard, BAG-1 has been shown to bind the ATPase domain of Hsc70, promote ADP/ ATP exchange and thereby modulating the chaperone activity in vitro HoÈ hfeld and Jentsch, 1997;Zeiner et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…The constitutively expressed Hsc70 was also shown to interact with BAG-1, an anti-apoptotic protein that binds to Bcl-2, although the functional impact of this interaction remains elusive. 122 Recently, it was shown that Hsp70 could interfere with the signal transduction Leukemia pathway leading to activation of JNK in response to stress. [123][124][125] Hsp27 belongs to the small Hsp subfamily, a group of proteins that vary in size from 15 to 30 kDa and share sequence homologies and biochemical properties such as phosphorylation and oligomerization.…”
Section: Modulation Of Drug-induced Cell Death By Heat Shock Proteinsmentioning
confidence: 99%